(untitled) (The Review of Diabetic Studies, 2025)
Background: Mechanical ventilation (MV) is a cornerstone intervention in critical care medicine, providing life-sustaining support for patients with acute respiratory failure. However, prolonged MV is associated with significant morbidity, including ventilator-associated pneumonia (VAP), ventilator-induced diaphragm dysfunction (VIDD), and increased mortality. The weaning process—the transition from mechanical support to spontaneous breathing—consumes approximately 40% to 50% of the total duration of ventilation. Traditional physician-directed weaning is often characterized by variability, delays in recognition of weaning readiness, and prolonged "dead time" where patients remain ventilated despite physiological recovery. Respiratory Therapist (RT)-led protocols have been proposed as a mechanism to standardize care, reduce variability, and accelerate liberation from MV. Objectives: This systematic review evaluates the efficacy of RT-led weaning protocols compared to physician-directed usual care in reducing the total duration of mechanical ventilation, weaning duration, and intensive care unit (ICU) length of stay (LOS). Secondary objectives include assessing safety outcomes (reintubation rates, mortality) and adverse events (VAP). Methods: A systematic review was conducted adhering to PRISMA guidelines. The PICO framework defined the eligibility criteria: Population (critically ill adults), Intervention (RT-led/driven protocols), Comparison (physician-directed/usual care), and Outcomes (MV duration, weaning duration, LOS, adverse events). Data were synthesized from randomized controlled trials (RCTs) and observational studies published up to 2023, encompassing diverse global healthcare settings. Results: The review synthesis indicates that RT-led protocols significantly reduce the total duration of mechanical ventilation (reductions ranging from 17% to 50% across studies) and weaning duration (reductions up to 70%). For example, landmark studies and recent trials demonstrate median reductions in ventilation time from days to hours in protocolized groups. Secondary outcomes show consistent reductions in ICU LOS and trends toward reduced VAP incidence. Safety analysis reveals no increase in reintubation rates or mortality, with some studies reporting significantly lower reintubation rates in protocolized arms. Conclusion: Respiratory Therapist-led weaning protocols represent a high-value, safe, and effective intervention for critically ill adults. By shifting from subjective, physician-dependent weaning to objective, RT-driven standardized care, healthcare systems can improve patient throughput, reduce complications, and optimize resource utilization.